Energy demand of a mechanized unit for the implementation of common bean crops - Wilson de A. Orlando Junior; Haroldo C. Fernandes; Paulo R. Forastiere; Tiago M. Guazzelli; Guilherme de M. Araújo (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Adequate soil managements and use of agricultural machinery are essential for the economic viability of these practices and for the environmental preservation. In this context, sowing and fertilizer application practices are the most important activities, since they affect crop development and present high energy demand. Therefore, the objective of this study was to evaluate the energy demand of a tractor-planter-fertilizer unit for the sowing of common bean seeds in no-tillage system as a function of three soil water contents (28.7, 36.4, and 47.6%) and three soil fertilizer placement depths (0.06; 0.11 and 0.15 m). The final common bean grain yield was also evaluated. The lowest energy demand was found for the highest soil water content combined with the lowest soil fertilizer placement depth. The highest common bean grain yield was found for plants under soil water content of 36.4% and fertilizer placement depth of 0.11 m, reaching 4,186 kg ha-1.